Is Discussing Identity More Important Than Shared Identity To Student-Staff Relationship Building? - Bovill, Catherine; Croft, Ashton; Dean Glover, Caroline; Felten, Peter (Teaching and Learning Inquiry, 2023)
Research consistently demonstrates that the quality of student-staff interactions matters for positive student outcomes. Some research studies also suggest that identity similarities (homophily) often contribute to meaningful human connections. Yet, the influence of student and staff identities on teaching and learning in higher education is less explored. We report on how undergraduate students and staff at one US university perceive the impact of identities on student-staff classroom relationships. Four themes emerged from our analysis: (1) Shared interests may be more important than shared identity for some students and staff; (2) Students’ year of study influences their views on staff identity and student-staff relationships; (3) Identity homophily is a point of connection for some students and staff; (4) Discussing identity, without identity homophily, can lead to positive course-based connections. The first three of these themes align with existing literature, but the fourth theme extends previous research, and we focus on exploring how for some students, discussing identities may be more important than matching identities when interacting with academic staff. Click here to read the corresponding ISSOTL blog post.